ON THE DEVELOPMENT OF ADIPOSE EYELIDS IN THE FRY OF LIZA MACROLEPIS AND L. PARSIA - Rengaswamy, C P (Indian Journal of Fisheries, 2011)
The adipose eyelid, a fatty tissue deposition on the eye which at times mayintrude over the orbit, is one of the important taxonomic characters used by severalworkers for distinguishing the different genera and sepcies of mullets. But there isconsiderable confusion regarding the formation of adipose eyelids in mullets. Lizawas proposed as a subgenus to include those without an adipose eyelid. As thereare all stages of obsolescence of eyelids, this character was never satisfactorythough the name was used generically and sub-generically by several workers.